THE USE OF BIBLIOGRAPHIC RESOURCES IN DOCTORAL THESES. THE RIGHT TO A CITATION WITH SPECIAL REFERENCE TO COURT RULINGS. THE USE OF INFORMATION PROVIDED BY AI TOOLS - Livia-Daniela STURZA (Challenges of the Knowledge Society)
Using bibliographic resources and quoting court judgements in academic works requires maximum attention to legal and ethical aspects, especially in the emergence of AI tools such as ChatGPT. This study analyses the challenges and recommendations regarding the correct integration of sources, observing specific citation rules (ISO, APA, or institutional guidelines) and copyright provisions. In the case of court judgements, the emphasis is on identifying the essential elements: ECLI code, file number, court, and date to ensure transparency and verifiability, but with the anonymisation of the identification data of the participants to ensure compliance with personal data. Regarding ChatGPT, the dilemmas related to copyright over AI-generated content are examined, given their lack of legal personality. Information and data provided exclusively by algorithms do not benefit from copyright protection, as deduced from the lack of such a provision in copyright law. At the same time, the risks of plagiarism and the need to explicitly declare the use of AI in research are highlighted. The paper highlights the importance of adapting academic and legal practices to technological developments, promoting a balance between innovation and legal compliance. Recommendations include updating quotation guidelines, awareness campaigns, and monitoring legislative frameworks in AI.